Impact of demographic and psychosocial factors on hysterosalpingography pain and discomfort - Anthony C. Ugwu; Augustine O. Imo; Okey F. Erondu (AOSIS, 2009)
Background: Hysterosalpingography (HSG) is an important diagnostic procedure in the investigation of infertility. It is the radiographic delineation of uterine and tubal cavities and is part of the diagnostic evaluation of conjugal infertility. This diagnostic procedure is associated with high levels of anxiety, pain and stress from various causes. This study was designed to investigate the impact of demographic and psychosocial factors on HSG pain and discomfort. Objective: The objective of this study was to determine the impact of demographic and psychosocial factors on hysterosalpingography pain and discomfort. Method: One hundred hysterosalpingography referrals were recruited for this study. Verbal detector scales were used to assess pain perception, Likert scales were used to assess the psychosocial variables, while visual analogue scales were used to assess discomfort. Pearson's correlations were conducted. Tests were two-tailed, with p < 0.05 indicating statistical signifcance. Results: Some of the patients (34%) indicated that the administration of analgesics prior to the procedure reduced the pain and discomfort associated with the procedure. Mean ± standard deviation of pain and discomfort were 2.82 ± 0.77 and 6.36 ± 2.19 respectively. Age correlated signifcantly with pain perception (r = -0.22, P < 0.05), while pain correlated signifcantly with perception of discomfort (r = -0.46, P < 0.05). Conclusion: Age signifcantly correlated with pain. This is a factor that could be harnessed for clinical use.